The importance of the choice of text book in studying and teaching thermodynamics - Awang, Mariyamni; Mat, Ramli (2004)
While it is generally true for most science and engineering subjects that an appropriate textbook can immensely aid a student in achieving the objectives of the subject, the study of thermodynamics at our faculty is even more dependent on it. Our students often have little knowledge of the hardware given in the subject, English is now the language of instruction and there is little repetition of the subject matter in other subjects. Ideally, many books ought to be considered before choosing a text, but given the large amount of literature available, we had considered two books in our study that aimed to find a suitable text. While the authors preferred one book, more than 63 % of the students preferred the other book based on its simple English, sufficient description of the systems and clear explanations. About 15 % of the students preferred a book in Malaysian.